2018
DOI: 10.1002/piq.21285
|View full text |Cite
|
Sign up to set email alerts
|

Building Psychological Capital and Employee Engagement: Is Formal Mentoring a Useful Strategic Human Resource Development Intervention?

Abstract: The popularity of formal mentoring has grown substantially in recent years. Literature has demonstrated individual‐level benefits such as learning, career planning, and enhancement of leadership as well as the acquisition of managerial skills from formal mentoring programs within work organizations. The primary purpose of this study was to examine whether and how formal mentoring programs could impact psychological capital and employee engagement, two key business drivers that can directly affect an organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Psychological capital has been considered state-like from the perspective of the state-trait continuum, so it is relatively adaptable and not as resistant to change as trait-like constructs such as personality traits (Luthans et al, 2007). Therefore, individual psychological capital can be fostered through training (Luthans et al, 2008(Luthans et al, , 2010 and, for example, through elements like authentic leadership (Woolley et al, 2010) or mentoring (Ghosh et al, 2018). Luthans and Youssef-Morgan (2017) report psychological capital development interventions as typically lasting 2 or 3 h and focusing on the four dimensions (hope, optimism, self-efficacy and resilience).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Psychological capital has been considered state-like from the perspective of the state-trait continuum, so it is relatively adaptable and not as resistant to change as trait-like constructs such as personality traits (Luthans et al, 2007). Therefore, individual psychological capital can be fostered through training (Luthans et al, 2008(Luthans et al, , 2010 and, for example, through elements like authentic leadership (Woolley et al, 2010) or mentoring (Ghosh et al, 2018). Luthans and Youssef-Morgan (2017) report psychological capital development interventions as typically lasting 2 or 3 h and focusing on the four dimensions (hope, optimism, self-efficacy and resilience).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Inspired by Greek mythology, a mentor is generally a person who possesses certain qualities or is in a position of authority, and who kindly watches over a younger individual so that he or she may benefit from the mentor's support and advice. Mentoring support occurs in different contexts, for example, and without limitations, in supporting disadvantaged youth (Preston et al, 2019), students at risk (Heppen et al, 2018), people entering challenging careers such as nursing (Williams et al, 2018) or teaching (Talbot et al, 2018), or more generally, in any kind of organisation that aims to develop its workforce (Ghosh et al, 2019). In an entrepreneurial context, although other definitions are possible, mentoring is a support relationship between a novice entrepreneur (where lack of experience is key), referred to as a 'mentee', and an experienced business person, referred to as a 'mentor', where the latter helps the former develop as a person.…”
Section: Ese and Mentoringmentioning
confidence: 99%
“…M1 asserted that Millennial workers should be mentored rather than solely given tasks to complete. Ghosh, Shuck, Cumberland, and D'Mello (2019) found that coaching and mentoring were influential in employee engagement. Leaders who promote coaching and mentoring could potentially create workplace relationships based on meaning and worth.…”
Section: Resultsmentioning
confidence: 99%